Supermoon Drives Beach Morphological Changes in the Swash Zone. Issue 22 (18th November 2020) - Banno, Masayuki; Kuriyama, Yoshiaki
Abstract: The effect of the supermoon, which appears much larger than a normal full moon, on the morphological changes of a sandy beach was investigated by analyzing a 25‐year daily observation data set of beach morphology in the swash zone. The beach morphology fluctuated in two cycles related to the supermoon: the semisynodic month cycle (from full moon to new moon, and vice versa) and the anomalistic month cycle (from perigee to perigee). The supermoon makes the erosion of the upper swash zone more likely by generating a larger tidal range. The high‐water‐level contour positions observed during supermoons retreated significantly, although there were no trends in the change for all the observations. Erosion due to high waves coincident with a supermoon can be expected to be more severe in the upper swash zone; including the supermoon effect in beach morphodynamic models can improve coastal management. Plain Language Summary: A "supermoon" is a full moon that appears much larger than a normal full moon. It causes an unusually high tide known as a "king tide, " and it increases the risk of coastal inundation. However, beach morphological changes induced by supermoons have not been investigated despite the effect of such changes on the vulnerability of coastal regions to inundation. Here, we show the correlation between the morphological changes (erosion and accretion) across the beach and the moon cycles using long‐term beach observation data. Our results indicate that the supermoon increases the risk of more severe beach erosion near the shoreline. The erosion is caused by a larger tidal range resulting from a stronger lunar gravitational force. The findings emphasize the importance of understanding the extreme erosion and inundation caused by the supermoon effects, particularly when combined with high waves and storm surges. Key Points: The beach morphology fluctuates in two cycles related to the supermoon: the semisynodic month cycle and the anomalistic month cycle A supermoon makes the beach erosion of the upper swash zone more likely by generating a larger tidal range Water‐level fluctuations based on predicted tides are an important factor for accurate estimation of beach erosion and accretion